2020
DOI: 10.24251/hicss.2020.319
|View full text |Cite
|
Sign up to set email alerts
|

Who is Influencing the #GDPR Discussion on Twitter: Implications for Public Relations

Abstract: On May 25, 2018, the European Union (EU) implemented the General Data Protection Regulation (GDPR) to protect individuals' privacy and data. This regulation has far-reaching implications as it applies to any organization that deals with data of EU residents. By studying the discussion about this regulation on Twitter, our goal is to examine public opinions and organizational public relations (PR) strategies about GDPR. The results show that the regulation is being actively discussed by a variety of stakeholder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…In a similar study, Grudz et al studied the discussion about the GDPR in a broad sense with the aim of examining public opinions and organizational public relations strategies about the GDPR [10]. Researchers collected tweets with the hashtag #gdpr and applied social network analysis to find opinion leaders.…”
Section: Gdpr-related Discussion On Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study, Grudz et al studied the discussion about the GDPR in a broad sense with the aim of examining public opinions and organizational public relations strategies about the GDPR [10]. Researchers collected tweets with the hashtag #gdpr and applied social network analysis to find opinion leaders.…”
Section: Gdpr-related Discussion On Social Mediamentioning
confidence: 99%
“…Their results indicate that the GDPR is being actively discussed by a variety of stakeholders, but especially by cyber-security and IT-related firms and consultants. One of the most interesting finding has been reported as that some of the stakeholders that were expected to have a more active role were less involved, including companies that store or process personal data, government and regulatory bodies, mainstream media, and academics [10].…”
Section: Gdpr-related Discussion On Social Mediamentioning
confidence: 99%
“…First, the implementation of the General Data Protection Regulation (GDPR) by the European Union (EU) on May 25, 2018, has generated active discussion by a variety of stakeholders. In their article titled "Who is Influencing the #GDPR Discussion on Twitter: Implications for Public Relations," Gruzd, Abul-Fottouh, and Mashatan [4] analyze the discussions about this regulation on Twitter and examine public opinions and organizational public relations (PR) strategies. The results show that cybersecurity and IT-related firms and consultants were actively involved in the discussion, but not other stakeholders, including companies that store or process personal data, government and regulatory bodies, mainstream media, and academics-were found less involved.…”
Section: Summary Of Articlesmentioning
confidence: 99%
“…In one of the related studies [23], Gruzd et al studied GDPRrelated discussions to examine public opinions and organizational public relations (PR) strategies about the GDPR. For this purpose, they collected all public tweets mentioning the #GDPR hashtag during a period of 6 months.…”
Section: Background and Related Workmentioning
confidence: 99%
“…It was reported that the GDPR was being actively discussed by a variety of stakeholders, especially by cyber security and IT-related firms and consultants. However, some of the stakeholders that were expected to have a more active role were salient, which included companies that store or process personal data, government and regulatory bodies, mainstream media, and academics [23].…”
Section: Background and Related Workmentioning
confidence: 99%